The Association Between Physical Activity with Nutritional Status of Adolescents During the COVID-19 Pandemic in Medan City - Erni Rukmana; Tyas Permatasari; Esi Emilia (Jurnal Dunia Gizi, 2020)
Background; nutritional status is a condition in which a person's body is healthy or not, which can be seen anthropometrically, biochemically, physically, and dietary intake. The state of excess intake and inadequate activity will lead to excess body weight. During the COVID-19 pandemic, physical activity decreased among adolescents, so there is a risk of being overweight. Objectives; to analyze the relationship between activity and nutritional status in adolescents during the COVID-19 pandemic in Medan City. Material and Method; analytical survey with cross-sectional study approach. This research was conducted by collecting data online in Medan City. The sample of this study was adolescents with a random sampling of 99 samples. Results; This study shows that there is a association between physical activity and nutritional status in adolescents with p-value (0,008). Conclusion; physical activity is needed to maintain body weight during the COVID-19 pandemic.